2016
DOI: 10.1111/jerd.12195
|View full text |Cite
|
Sign up to set email alerts
|

Shade Correspondence, Color, and Translucency Differences between Human Dentine and a CAD/CAM Hybrid Ceramic System

Abstract: The results of the present study could help clinicians in their decision of choosing a specific shade and translucency for their anterior or posterior esthetic restorations with hybrid ceramics. (J Esthet Restor Dent 28:S46-S55, 2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 49 publications
(97 reference statements)
0
31
0
4
Order By: Relevance
“…However, this situation also results in increased opacity. As a general rule, the relationship between strength and esthetics is inversely proportional . In the present study, the reason why VITA Enamic has a lower translucency than other resin–ceramic hybrid materials might be related to its Al 2 O 3 content (approximately 23% by weight).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, this situation also results in increased opacity. As a general rule, the relationship between strength and esthetics is inversely proportional . In the present study, the reason why VITA Enamic has a lower translucency than other resin–ceramic hybrid materials might be related to its Al 2 O 3 content (approximately 23% by weight).…”
Section: Discussionmentioning
confidence: 55%
“…As a general rule, the relationship between strength and esthetics is inversely proportional. 27,46 In the present study, the reason why VITA Enamic has a lower translucency than other resin-ceramic hybrid materials might be related to its Al 2 O 3 con- 27 also evaluated the translucency properties of Cerec CAD-CAM materials; VITA Mark II presented with more translucency than IPS e. max CAD at both 0.5 and 1.0-mm thicknesses. Similar results were observed in the present study where the translucency of IPS e.max CAD was significantly lower than that of VITA Mark II, confirming that the amount of crystallin affects translucency.…”
Section: Discussionmentioning
confidence: 67%
“…Also, to complete the 14‐day of treatment period with at‐home bleaching agents, the specimens were left in distilled water more than in the in‐office bleaching agents, which may increase water sorption. It has been demonstrated that water sorption can lead to softening of the matrix, the release of unreacted monomers, and the degradation as well as leaching of filler particles . Taking these reports into consideration, the higher translucency differences after using at‐home bleaching agents may be attributed to changes of the refractive indices due to the water molecules absorbed by the materials.…”
Section: Discussionmentioning
confidence: 99%
“…This newly introduced formula could have provided a higher degree of fit for both color difference perceptibility and acceptability. 53,54 …”
Section: Discussionmentioning
confidence: 99%